Location-aware spatial keyword search for spatial web objects - Wang, Chun An (2011)
Given the use of 3G mobile devices is rapidly taking over the current mobile phone market and with the increase in the usage of GPS systems on vehicles around the word, a lot of applications that uses the spatial database have quickly emerged as a new segment for software industry in mobile applications.